Exploring the Relationship between SLC30A8 Gene Polymorphism and Type 2 Diabetes Susceptibility in District Vehari, Pakistan - Fatima Ghafoor,; Samreen Riaz, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Type 2 diabetes mellitus (T2DM) is estimated to afflict 537 million individuals globally and has reached an epidemic scale. These global estimates are to develop innovative preventive and treatment methods and to put these methods into action. To investigate if SLC30A8 gene polymorphisms can be used to predict the onset of T2DM in residents of Punjab, Pakistan, two groups were established based on prospective follow-up of appropriate population samples. Males made up 29.6% and women 70.4% of the T2DM unit. Deoxyribonucleic acid (DNA) was separated. Polymerase chain reaction or PCR was used for genotyping, and real-time PCR was then conducted. The statistical analysis was performed utilizing the statistical package SPSS 16.0 software program. The SLC30A8 gene genotype TT rs13266634 was linked to an increased risk of type 2 diabetes mellitus (T2DM) (relative risk — RR 1.51, 95% confidence interval — CI 1.11 – 2.05, p = 0.008). A protective benefit against T2DM was linked to the SLC30A8 gene's CC genotype, rs13266634 (RR 0.57, 95% CI 0.35 – 0.92, p = 0.026). The T2DM group comprised 442 individuals in the District Vehari. The average age at the time of the initial screening was 56.2 ± 6.7 years. 531 individuals without diabetes were chosen to serve as controls; their average age was 56.1 ± 7.1 years. In the control group, the frequencies of single nucleotide polymorphisms (abbreviated as SNP) match the expected frequencies as per the Hardy–Weinberg equilibrium. The SLC30A8 gene's rs13266634 polymorphism shows its correlation with the likelihood of developing T2DM and can be a potential candidate for a diabetes risk score.